Association between dietary fiber intake and risk of coronary heart disease: A meta-analysis. Issue 4 (August 2015) - Wu, Yihua; Qian, Yufeng; Pan, Yiwen; Li, Peiwei; Yang, Jun; Ye, Xianhua; Xu, Geng
Summary Background & aims The association between coronary heart disease (CHD) and dietary fiber intake is not consistent, especially for the subtypes of dietary fiber. The aim of our study was to conduct a meta-analysis of existing cohort published studies assessing the association between dietary fiber intake and risk of CHD, and quantitatively estimating their dose–response relationships. Methods We searched PubMed and EMBASE before May 2013. Random-effect model was used to calculate the pool relative risk (RRs) for the incidence and mortality of CHD. Dose–response, subgroup analyses based on fiber subtypes, heterogeneity and publication bias were also carried out. Results Eighteen studies involving 672, 408 individuals were finally included in the present study. The pooled-adjusted RRs of coronary heart disease for the highest versus lowest category of fiber intake were 0.93 (95% confidence interval (CI), 0.91–0.96, P < 0.001) for incidence of all coronary events and 0.83 (95% CI, 0.76–0.91, P < 0.001) for mortality. Further subgroup analyses based on fiber subtypes (cereal, fruit, and vegetable fiber), indicated that RRs were 0.92 (95% CI, 0.85–0.99, P = 0.032), 0.92 (95% CI, 0.86–0.98, P = 0.01), 0.95 (95% CI, 0.89–1.01, P = 0.098) respectively for all coronary event and 0.81 (95% CI, 0.72–0.92, P = 0.001), 0.68 (95% CI, 0.43–1.07, P = 0.094), 0.91 (95% CI, 0.74–1.12, P = 0.383) for mortality. In addition, a significant dose–response relationship was observed between fiber intake and the incidence and mortality of CHD (P < 0.001). Conclusions Our results indicate that consumption of dietary fiber is inversely associated with risk of coronary heart disease, especially for fiber from cereals and fruits. Besides, soluble and insoluble fibers have the similar effect. A significant dose–response relationship is also observed between fiber intake and CHD risk.